(untitled) (The Dhaka University Journal of Earth and Environmental Sciences, 2022)
The study is an attempt to explore the existing status of urban poor’s healthcare services and problems in addition to showing a way out of the current situation. Primary data collection was qualitative and quantitative approaches. The study reveals a significant spatio-temporal variation considering the current healthcare situation. The overall status of current healthcare was found moderate to very poor and very severe in Sandwip Colony. The absence of public sector healthcare services was identified inside the three study sites. Besides, community hospitals and clinics were the burning issues for maternity and child healthcare along with the unavailability of seeking medicine, especially in the Sandwip Colony. The study concluded that the urgency of establishing a community hospital in the Shershah Colony and a maternity clinic in Burma & Sandwip Colony for free treatment, with specialist doctors, the availability of ambulance by the government and the NGOs. Moreover, community people could arrange medical campaigns and personal hygiene awareness programs in their locality. Further study and a structural policy are needed to formulate the improvement of the urban poor’s healthcare services in Chittagong city. The Dhaka University Journal of Earth and Environmental Sciences, Vol. 10(3), Special Issue 2022: 29-41